номер 107 гдз 8 класс алгебра Муравин Муравин

1)\begin{equation}x-\frac{a}{b}=1 \end{equation} \begin{equation}x=1-\frac{a}{b} \end{equation} \begin{equation}x=\frac{b-a}{b} \end{equation} 2)\begin{equation}x+\frac{b}{c}=2 \end{equation} \begin{equation}x=2-\frac{b}{c} \end{equation} \begin{equation}x=\frac{2c-b}{c} \end{equation} 3)\begin{equation}2x-\frac{p}{q}=\frac{a}{b} \end{equation} \begin{equation}2x=\frac{a}{b}+\frac{p}{q} \end{equation} \begin{equation}2x=\frac{aq+bp}{bq} \end{equation} \begin{equation}x=\frac{aq+bp}{2bq} \end{equation} 4)\begin{equation}\frac{n}{k}+\frac{x}{3}=\frac{b}{a} \end{equation} \begin{equation}\frac{x}{3}=\frac{b}{a}-\frac{n}{k} \end{equation} \begin{equation}\frac{x}{3}=\frac{bk-an}{ak} \end{equation} \begin{equation}x=\frac{3\left ( bk-an \right )}{ak} \end{equation} 5)\begin{equation}\frac{x}{2a}+\frac{x}{a}=1 \end{equation} \begin{equation}\frac{x}{2a}+\frac{x}{a}=1 \end{equation} \begin{equation}\frac{x+2x}{2a}=2a \end{equation}
3x = 4a² \begin{equation}x=\frac{4a^{2}}{3} \end{equation} 6)\begin{equation}\frac{x}{3a}-\frac{x}{4a}=\frac{1}{6} \end{equation} \begin{equation}\frac{x}{3a}-\frac{x}{4a}=\frac{1}{6} \end{equation} \begin{equation}\frac{4x-3x}{12a}=\frac{2a}{6} \end{equation} \begin{equation}\frac{x}{12a}=\frac{2a}{6} \end{equation} \begin{equation}x=\frac{2a\cdot 12a}{6}=4a^{2} \end{equation}
x = 4a²
7)\begin{equation}\frac{x-1}{4}-1=\frac{a}{b} \end{equation} \begin{equation}\frac{x-1}{4}-1=\frac{a}{b} \end{equation} \begin{equation}\frac{x-1}{4}=\frac{a}{b}+1 \end{equation} \begin{equation}\frac{x-1}{4}=\frac{a+b}{b} \end{equation} \begin{equation}x-1=\frac{4\left ( a+b \right )}{b} \end{equation} \begin{equation}x=\frac{4\left ( a+b \right )}{b}-1=\frac{4a+4b-b}{b}= \end{equation} \begin{equation}=\frac{4a+3b}{b} \end{equation} \begin{equation}x=\frac{4a+3b}{b} \end{equation} 8)\begin{equation}\frac{x+2}{3}+1=\frac{b}{a} \end{equation} \begin{equation}\frac{x+2}{3}=\frac{b}{a}-1 \end{equation} \begin{equation}\frac{x+2}{3}=\frac{b-a}{a} \end{equation} \begin{equation}x+2=\frac{3\left ( b-a \right )}{a} \end{equation} \begin{equation}x=\frac{3\left ( b-a \right )}{a}-2=\frac{3b-3a-2a}{a}= \end{equation} \begin{equation}=\frac{3b-5a}{a} \end{equation} \begin{equation}x=\frac{3b-5a}{a} \end{equation}